Managing change in organizations : a practice guide. - Project Management Institute (Newtown Square, Pennsylvania : Project Management Institute, Inc., 2013)
This practice guide begins by providing the reader with a framework for creating organizational agility and judging change readiness. It then explores organizational change from three different management perspectives: portfolio, program and project. it therefore equips the reader with practical techniques on successfully designing, creating, implementing and sustaining organizational change.
"Project Management Institute Global Standard"--Cover.
Includes bibliographical references (page 115) and index.
oif 24/06/15
Loan
Keywords: Organizational change -- Management; Project management -- Standards